A Case-Specific Instance of Media Capture: the Gorilla Case of Slovakia - Školkay, Andrej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
This article discusses an instance of case-specific self-inflicted partial media capture, acknowledging the chilling effect of legislation consistent with partial state capture. In general, this case illustrates the ethical and legal dilemmas in the reporting of a specific type of large-scale corruption in the media, which involves the denial of all accusations by most sources and a controversial stand by state authorities and politicians on the issue, forcing the media to primarily report rumors or contradictory claims and denials (after controversial files regarding the corruption were made public anonymously on the internet) or desist from reporting altogether (before the files were made public on the internet, due to possible libel threats). The findings question the normative expectations expressed in democratic theory related to the role of the media as a watchdog, in the specific context of large-scale corruption in post-communist states. Moreover, this paper suggests the need to re-examine the methodological aspects of quantitative content analysis of media coverage of corruption. This paper has also attempted to update the emerging theory on media capture with the term partial case-specific media capture.